ANALYSIS OF EPIDEMIOLOGICAL STUDIES IN PHYSICAL ACTIVITY IN NORTHEASTERN BRAZIL (Fiep Bulletin - online, 2016)
The epidemiological study as a research tool on the health-disease, is growing, including in the field of physical activity. In Brazil, this production was started later, and currently, there is an evolution of research on physical activity, however, regional differences are observed in the publications, where most studies are conducted in the Southeast and South. The objective was to present the main features and research proposals developed in the Northeast (Alagoas, Bahia, Ceará, Maranhão, Paraíba, Pernambuco, Piauí, Rio Grande do Norte and Sergipe), in the study of physical activity epidemiology. Literature search in databases Lilacs and Scielo. The following descriptors in Portuguese language being used: "epidemiology"; "physical activity"; "Physical aptitude"; "sedentary lifestyle"; "Risk Factors" and "physical education". To characterize as epidemiological studies should present the title, abstract or methodology epidemiological study description (observational or experimental). Selected studies in the form of paper, between the years 2010-2015 and who used some sort of health-disease process related to physical activity and excluded: studies did not assess physical activity focus; published in Portuguese; that have not been developed only in the states surveyed area and review articles, theses and dissertations. Identified 25 articles that met the inclusion criteria. The results identified 11 articles published in Bahia, eight in Pernambuco, Alagoas and Ceará with two publications, and Paraíba and Maranhão to an article respectively. Among the descriptors found the term "physical activity (motor)" was the most cited, followed by "physical fitness" and "inactivity". Being more surveyed teens (school) and the elderly, the instrument with greater use was the questionnaire (recalls) and between models of epidemiological studies the cross-sectional study (prevalence) was the most used. A regional disparity, however, an increase in the number of scientific publications identified yet.
Keywords: Epidemiology of Physical Activity. Epidemiological study. Northeast. Brazil.